Families of algebraic and continuous maps to projective space - Aumonier, Alexis (Mathematica Scandinavica, 2025)
We explain how results comparing the homology of spaces of algebraic and continuous maps to projective spaces can be leveraged to compare moduli stacks of families of algebraic and continuous maps.